Development of Just in Time Teaching (JITT) Based on a Scientific Approach on Mushroom Materials to Improve Analytical Thinking Ability of Class X Senior High School Students - Adella Adella; Nurhayati Nurhayati; Masduki Asbari (Universitas Muhammadiyah Enrekang, 2022)
This study aims to: 1) Develop a JiTT based on a scientific approach, 2) Find out the feasibility of a JITT based on a scientific approach, 3) Find out the effectiveness of a JITT based on a scientific approach to improve analytical thinking skills for class X SMA on mushrooms. This study uses the Research and Development (R & D) referring to the Borg & Gall model with the stages: 1) research and information gathering, 2) planning, 3) initial product development, 4) initial trial, 5) first product revision, 6) limited field test, 7) second product revision, 8) operational field test, 9) third product revision, 10) dissemination. The feasibility of the model was validated by model experts, material experts, biology teachers (practitioners), and students. Data were collected using questionnaires, observation sheets, interviews, and tests. The research data were analyzed using qualitative descriptive and quantitative descriptive methods. Analytical learning ability was analyzed using a t-test (t-test) with a posttest-only control group design. Based on the results of the study, it can be concluded as follows: 1) the development of JiTT is carried out by taking into account the characteristics of the model, namely the syntax, social system, support system, student role, teacher role, instructional impact, and accompaniment impact, 2) the results of model development learning JiTT is feasible to be applied to mushroom material. Learning model JiTT based on the assessments of experts, practitioners, and student responses which overall gave a good category to product development, 3) the JiTT able to improve students' analytical thinking skills. Statistical tests on analytical thinking ability showed that there was a significant difference (sig 0.00 < 0.05) between the control class and the experimental class.